Gendered racial disparities in health of parents with children with developmental disabilities - Lee, Juha; Gao, Manjing; Lee, Chioun (Frontiers in Psychology, 2022)
Abstract Background: There is little information on (1) how adverse experiences in early life are associated with the risk of having a child with health problems and (2) whether the health of racial and gender minority groups would be particularly compromised if they have developmentally disabled (DD) children. Objective: By integrating life-course perspectives and the intersectionality framework, we examine (1) the extent to which parents’ early-life adversities (ELAs) are associated with having children with DD or other health issues and (2) whether the association between having DD children and parental (physical and mental) health varies across race–gender groups after accounting for ELAs. Methods: Using data from Black and White parents from the Midlife in the U.S. Study (n=7,425; 18% Black), we employed (1) multinomial logistic regression models to investigate the degree to which ELAs are associated with parenting types (having a child with DD, a child with recent illness, or a child without these health issues) and (2) multiple regression models with a three-way interaction term to investigate whether the gender–parenting type association differs by race. Results: With more adversities, the probability of having children with health issues increases for all race–gender groups, but most dramatically for Black women. Having DD children is associated with more chronic illnesses and functional limitations for women than men, with the largest burden for Black women, yet neither gender nor racial differences in depressive symptoms. Our results highlight that while raising children with DD takes a toll on the health of all parents, the strain might be larger for Black mothers. Conclusion: The adverse effects of parenting a child with DD is more pronounced for Black women than for other race–gender groups indicating opportunities to promote community-based programs for these parents.